Efecto de la levadura hidrolizada de cerveza (Saccharomyces cerevisiae) como promotor de crecimiento en cerdos - Ormaza Vera, Enrique Javier (2019)
The main objective of this research is to evaluate the effect of hydrolyzed brewer's yeast on the feeding of pigs from the cross between Landrace x Pietran breeds from weaning day (28) today 84, in health and productive parameters, with economic estimate. Six pigs were allocated for each treatment (three females and three males), with a total of 18 experimental units. A DBCA was used with three replicates in arrangement of factorial treatments, the factors being: yeast levels (0 mL, 10 mL and 20 mL) and sex (females and males). Productive variables (food consumption, weight gain, nutritional conversion and final weekly weight) and health variables (mortality, presence of diarrhea, red blood cell count, white blood cell count, hematocrit and hemoglobin) were measured. The results obtained for food consumption were highly significant with values of 6.77 kg in the dose at 20 mL, in weight gain there were significant differences with values of 3.05 kg in the dose of 20 mL, in the conversion feeding were highly significant with values of 2.27 kg at a dose of 20 mL and the final weight in the 12 weeks was found highly significant differences with values of 29.17 kg in males and 29.08 kg in females at the dose of 20 mL. For this reason, it is concluded that brewer's yeast is an alternative to complement the feeding of pigs in the growth stage.